2009
DOI: 10.1128/aac.01467-08
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Posaconazole and Other Antifungal Agents against Mucorales Strains Identified by Sequencing of Internal Transcribed Spacers

Abstract: The antifungal susceptibility profiles of 77 clinical strains of Mucorales species, identified by internal transcribed spacer sequencing, were analyzed. MICs obtained at 24 and 48 h were compared. Amphotericin B was the most active agent against all isolates, except for Cunninghamella and Apophysomyces isolates. Posaconazole also showed good activity for all species but Cunninghamella bertholletiae. Voriconazole had no activity against any of the fungi tested. Terbinafine showed good activity, except for Rhizo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
67
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 29 publications
(28 reference statements)
12
67
4
Order By: Relevance
“…Most cases had previously been managed in a manner similar to that employed with our patient, with amphotericin B and surgical debridement treatment. Recent reports have shown that posaconazole has a good in vitro response (MIC, 0.1 g/liter) (16,17,18) as well as in vivo response (3,16,18), although in the reported cases of mucormycosis due to Apophysomyces trapeziformis, as with the Joplin tornado, only 6 of 13 patients responded to treatment with that compound (6,19).…”
Section: Figmentioning
confidence: 93%
“…Most cases had previously been managed in a manner similar to that employed with our patient, with amphotericin B and surgical debridement treatment. Recent reports have shown that posaconazole has a good in vitro response (MIC, 0.1 g/liter) (16,17,18) as well as in vivo response (3,16,18), although in the reported cases of mucormycosis due to Apophysomyces trapeziformis, as with the Joplin tornado, only 6 of 13 patients responded to treatment with that compound (6,19).…”
Section: Figmentioning
confidence: 93%
“…Practical reasons for this are the difficulties of cultivating these fungi from biopsy samples (22,34) and of differentiating zygomycete species by classical mycological techniques in clinical microbiology laboratories. Previous com-prehensive studies on susceptibility profiles against antifungal drugs in the Mucorales revealed considerable variation among and within genera and species, as defined either by applying classical parameters (5,16,35,39,40) or more recently by using molecular taxonomic methods (1,12). A recent review of in vitro activity of antifungals against zygomycetes was provided by AlastrueyIzquierdo et al (2).…”
mentioning
confidence: 99%
“…For this reason, and because of the difficulty of morphological species identification, studies on the taxon specificity of susceptibility profiles in this group of fungi need to be preceded by molecular identification of the strains under study (1). Otherwise, in clinical practice, when the only intention is to determine the most appropriate antifungal as quickly as possible, susceptibility tests could also be performed directly.…”
mentioning
confidence: 99%
“…Identification of the species may be important to gain better knowledge of the epidemiology of zygomycosis and because the different species of Zygomycetes exhibited various antifungal susceptibilities (1,6,7). Species identification may thus be important to guide the choice of antifungal therapy.…”
Section: Discussionmentioning
confidence: 99%